2007
DOI: 10.1021/cm070425l
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanoporous Gold Film Electrodes with Ultrahigh Surface Area and Electrochemical Activity

Abstract: Nanoporous gold film (NPGF) electrode was fabricated by applying multicyclic potential scans on a polished gold electrode in an electrolyte composed of ZnCl 2 and benzyl alcohol. In the cathodic potential scan, Zn was first electrodeposited on the gold electrode surface, and Au-Zn alloy was then directly formed on the surface under an elevated temperature. In the subsequent anodic potential scan, dealloying of Zn took place, resulting in a nanostructured gold film. Furthermore, Zn was then electrodeposited ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(176 citation statements)
references
References 24 publications
4
167
0
1
Order By: Relevance
“…Ligament sizes ranging from 10 nm-60 nm have been reported as have surface areas that are 200x greater than a planar gold substrate [68]. In a related method, the electrochemical alloying/dealloying process took placed on gold electrodes placed in an electrolyte prepared using ZnCl 2 and benzyl alcohol (BA) at elevated temperatures [173]. Figure 10 shows an SEM image of nanoporous gold fabricated by alloying/dealloying in the ZnCl 2 /BA at 120 ∘ C [173].…”
Section: Other Nanoporous Gold Sensorsmentioning
confidence: 99%
“…Ligament sizes ranging from 10 nm-60 nm have been reported as have surface areas that are 200x greater than a planar gold substrate [68]. In a related method, the electrochemical alloying/dealloying process took placed on gold electrodes placed in an electrolyte prepared using ZnCl 2 and benzyl alcohol (BA) at elevated temperatures [173]. Figure 10 shows an SEM image of nanoporous gold fabricated by alloying/dealloying in the ZnCl 2 /BA at 120 ∘ C [173].…”
Section: Other Nanoporous Gold Sensorsmentioning
confidence: 99%
“…[21][22][23][24] Currently, nanoporous gold films (NPGF) have attracted attention for their widespread application in catalysis and in the sensors field because of their higher surface area in comparison to bulk gold electrodes, allowing superior electron transfer rate between the electrode-electrolyte interface. 25,26 Such platforms have been mainly prepared by alloying/dealloying or template methods, where hazardous chemicals are mostly used. 27,28 Hence, it is really a challenging task to develop convenient and green methods to fabricate NPGF with high surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic property of Au nanoparticles (NPs) mainly depends on their preparation methods [19,20]. Previously, Maduraiveeran et al [15] reported the concurrent sensing of N 2 H 4 , SO 3 2-, and NO 2 -with a large decrease in the overpotentials using a colloidal Au NPs-modified electrode.…”
Section: -mentioning
confidence: 99%